Postwar Kosovo: global and local dimensions of interethnic reconciliation processes - Ferati-Sachsenmaier, Flora (International journal of transitional justice, 2019)
This article examines how Kosovo’s postwar struggle for statehood intersected with interethnic reconciliation processes from 1999 to 2008. It argues that, among other factors, it was the ensuing governance in postwar Kosovo that made it difficult, if not impossible, for any kind of meaningful interethnic reconciliation to take place. Drawing on primary sources and personal interviews, the article focuses on groups that can be called ‘reconciliation agents’ and that were among the main actors dealing with the legacy of the Kosovo war. They were typically multiethnic actors, both in terms of their staff members and their declared agendas, and they were exceptionally creative and courageous in their efforts to promote interethnic reconciliation. They were, however, not seen as postconflict forces by much of the population and were often perceived as agents continuing the conflict over the status of Kosovo by other means. The same was true for their international donors and other relevant international governmental actors that were supporting interethnic reconciliation activities.